Technical Improvement in DNA Preparation for PulsedÃ¢â‚¬â€Field Gel Electrophoresis - Kwai Lin, Thong; Kin Seng, Lai; Yee Ling, Goh (Malaysian Journal of Science, 2003)
We report a rapid pulsed-field electrophoresis (PFGE) protocol for subtyping $Salmonella$ isolates. Modifications were made to reduce the number of steps and duration of proteolysis in our original protocol for the preparation of intact, genomic DNA for PFGE analysis. Comparison of PFGE patterns by independent researchers showed that subtyping results obtained using this modified, rapid protocol were highly reproducible.